A Vision for Population Health Management to Support Integrated Care - Hayes, Catherine (My University, 2022)
The concept of aggregating population data with data from multiple care and service settings, the analysis of that data into a single, actionable patient record, using the insights gained to identify their specific health care needs and to develop a tailored response to them through • use of data analytics, artificial intelligence and digital technologies, • by stratifying populations according to risk of deterioration in health. This allows faster access to, and greater accuracy of, diagnostic tests and use of personalised treatment plans.
Workshop SMART D8 - Optimising Data to Integrate Health and Social Care
Keywords: Digital Engagement; Inclusive Society; Making Ireland; Health informatics